Tawẓīf al-Sīnimā fī Ta‘līm al-Lughah al-‘Arabīyah li-Ghayr al-Naṭiqīna bi-hā: Bayn al-Āfāq, wa-al-Taḥaddiyāt, wa-al-Āliyāt, wa-al-Kayfiyāt - Aktiri Boujemaa Anass (Al-Ma‘rifah, 2018)
The issue of employing technological media, the film model in teaching Arabic to non-Arabic speakers, has become an urgent necessity dictated by the changing nature of global societies. Therefore, we find ourselves as Arab and Islamic societies in need of changing the pattern of our traditional visions of the educational process, as they no longer respond to the new learners’ tendencies of languages, which prompted us to propose an alternative that is in line with the new shifts in education and training; an alternative that employs movie and integrates it into the learning process because of the influential technical and aesthetic potential available, which can build educational content in a modern form. However, this proposition that we are establishing, despite the promising prospects, is not without its challenges that existentially impede its realization. According to the study, it is possible to overcome these difficulties if there are a vision and a will. Therefore, we find that the study has worked to give suggestions on the mechanisms and the modalities to prepare a creative and fruitful approach in the Arabic language for non-native speakers, depending on the skill of film viewing, which would give this new educational vision a deep strategic dimension that will bring the Arabic language into line with the language of modern technological media.